ETR 300: Speed Tech Auto Garage / Adzreen Ekhlas ... [et al.] - Ekhlas, Adzreen; Yusri, Dg Shamimi; Chambas, Mohd Shukri; Aras, Samsir; Osuan, Elni (2011)
Nowadays the markets of car accessories are increasing through the entire world. It is because of the high technology and modern that exists today. Not only that, the demand to change lifestyle too had lead these business get a great response especially the youths and in the average age. Our business is Speed Tech Auto Garage and the nature of the business is as the economic growth, the Demand for car navigation systems in Malaysia is expected to be 49.2% higher in 2011 compared to the estimated 104,400 units sold this year. The Developments in various sector have made auto accessories a hot selling commodity especially when the Automobiles offer a huge deal of comfort such as provides automotive aftermarket accessories, electronics, and glass repair and replacement while travelling and people can save valuable time than to rely on public transport. Auto accessories are sold the maximum to enhance the comfort and pleasure of both the passengers and drivers. Along with that, the need for style, looks, status display, increased comfort and enhanced luxury options have all contributed to the huge rise in demand for auto accessories. This business has a great opportunity to success because people will invest their money in order to upgrade and service their car for safety and interest. There are some company who success in doing car accessories business which is Fuji Car Accessories located in Putatan.